Recaudación de los impuestos y la Ejecución de proyectos de inversión pública en la Municipalidad Provincial de San Martín, periodo 2010-2014 - Escudero Saavedra, Marcelo Aarón (2016)
The research was aimed at studying how is carried raising taxes in the province of San Martin, then establish the link between the recollection of taxes and execution of public investment projects in the provincial municipality of San Martin, 2010-2014 period, in which data was collected by gathering information and then apply the Pearson correlation test in SPSS software, and get the results, concluding that: As to what concerning the municipal tax collection, this is growth from 2010, so the alternative hypothesis (HA) is adopted; Likewise we can see an improvement in the management of the implementation of public investment projects, it is concluded that the implementation of work in the provincial municipality of San Martin, is inconsistent because it can not say exactly, the budget assigned will run for an upcoming period, which also empowers management have the ability to define what works performed, finally in this research, having obtained and compared the results regarding the variables was determined that there is a relationship between the same, and a high degree of dependence, thus the alternative hypothesis was accepted